2006
DOI: 10.1111/j.1365-2648.2006.04060.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of turning with unequal time intervals on the incidence of pressure ulcer lesions

Abstract: More frequent repositioning on a pressure-reducing mattress does not necessarily lead to fewer pressure ulcer lesions and consequently cannot be considered as a more effective preventive measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(172 citation statements)
references
References 26 publications
(32 reference statements)
5
163
2
2
Order By: Relevance
“…A 6-hour turning sc hedule for patients lying on a viscoelastic mattress resulted in similar outcomes, but a 4-hour turning schedule for patie nts lying on a visc oelastic mattress signific antly reduced stage II PUs . Other research suggests that turning ma y need to occur more frequently than every 2 hours and that sufficient pressure reduction surfaces are needed in addition to turning [32,[34][35][36]. Recently, Vanderwee et al, using a pressu re-reducing mattress, found no difference between repositioning patient s every 4 hours and alternating between 2 hours in late ral and 4 h ours in supine [36].…”
Section: Turning Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…A 6-hour turning sc hedule for patients lying on a viscoelastic mattress resulted in similar outcomes, but a 4-hour turning schedule for patie nts lying on a visc oelastic mattress signific antly reduced stage II PUs . Other research suggests that turning ma y need to occur more frequently than every 2 hours and that sufficient pressure reduction surfaces are needed in addition to turning [32,[34][35][36]. Recently, Vanderwee et al, using a pressu re-reducing mattress, found no difference between repositioning patient s every 4 hours and alternating between 2 hours in late ral and 4 h ours in supine [36].…”
Section: Turning Frequencymentioning
confidence: 99%
“…Furthermore, in studies on turning, patients who are able will change posture between scheduled repositionings. As a result, these subjects are exposed to more position changes than offered by the intervention, which may mask a need for more frequent repositioning in those unable to reposition themselves [36]. The necessary repositioning frequency may be so high that implementation is impractical for immobile patients [32].…”
Section: Turning Frequencymentioning
confidence: 99%
“…The result observed in the variable Turning patients every two hours is similar to a study developed in the intensive care unit of a Brazilian teaching hospital, where, before educational intervention, of the 15 patients presenting PU only 13.3% were turned every 2 hours and, after intervention, none of the 15 patients who presented PU received this kind of preventive care (8) . Two studies conducted in geriatric units in Belgium demonstrated that in one of them, the group of patients with a 2-hour turning regimen and turning to supine position every 4 hours presented a 16.4%, PU levels II to IV incidence whereas the control groups who were turned every 4 hours presented a 21.2%, incidence with no statistically significant difference between the two groups (26) ; in another study, among the 14.3% patients who were turned every 2 hours, and the 3% who received this care every 4 hours presented statistically significant differences (27) . For the other care categories Clean and dry patients after incontinence episode, Prescribed and administered diet, Intake of fluid from 1500 to 2000 ml/day, Daily use of skin moisturizer and Use of adequate mattress, there were no studies in the literature whose methodologies enabled comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PUs are an indicator of the quality of the nurse-specific provided by health care organizations (8)(9)(10). In studies conducted before 2008-2009 reveal a reduction in the prevalence of PUs in hospitals (4%-20%), (4,(11)(12)(13)(14). However, the prevalence of PUs in intensive care units varies between 9% and 42% which is still frequent (15).…”
Section: Introductionmentioning
confidence: 99%